Impact of donor and procedural parameters on platelet yield in plateletpheresis: a retrospective data analysis over a seven-month period - Gorana Ahmetovic-Karic; Kenan Mehic; Selim Arifovic; Ajsa Zildzic; Faruk Bradaric (Medicinski glasnik, 2026)
Aim: To identify the donor and procedural parameters that influence the platelet yield obtained by apheresis. Methods: A retrospective observation study of 60 plateletpheresis in the Blood Transfusion Institute of Federation of Bosnia and Herzegovina in Sarajevo, was done. Plateletpheresis were performed using Amicus cell separator with platelet collection protocol, and in accordance with the work procedure of the institution. The results were compared using statistical correlation and statistical comparison between groups. The demographic and hematologic parameters of donors, as well as procedural characteristics were correlated with their platelet yield. P<0.05 was considered statistically significant. Results: The mean pre-donation platelet count was 252x10e9/L. Mean platelet yield was 3.5x10e11/unit. In the majority of donors, 48 (80%), amount of ˃3x10e11/unit was collected. Positive correlation was observed between platelet yield and pre-donation platelet count (r=0.611, p<0.000), blood volume processed (r=0.512, p<0.000), body weight (r=0.525, p<0.000), body height (r=0.264, p=0.042), and run time (r=0.514, p<0.000). Study also observed positive correlation between actual product platelet yield and the software predicted yield (r s =0.774, p<0,000) with statistical difference between them (p<0.000). Conclusions: Pre-donation platelet count, body weight, body height, blood volume processed and run time affected platelet yield. Optimizing the platelet yield is a matter of identifying the factors that influence the yield and thus the selection of donors, providing better quality platelet products and clinical outcomes.
Keywords: donor; plateletpheresis; platelet yield